2012
DOI: 10.1179/102453312x13221316477859
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone induces apoptosis by interacting with the JAK/STAT pathway in HL-60 and K-562 leukemic cells

Abstract: The JAK/STAT pathway components may play an important role in the apoptosis mechanism of leukemic cells under MP treatment in HL-60 and K-562 cells. Other pathways may also be involved with a post-translational modification seen in the HL-60 cell line, with both upregulation and downregulation of protein expression levels of STAT5B and STAT5A, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The regulation of various extracellular factors on cell behavior is closely related to the activation of intracellular multiple signaling transduction pathways. Among them, activation of the JAK/STAT pathway in cell apoptosis has been widely studied in recent years (2628). The JAK/STAT signaling pathway is one of the important pathways of cytokine transduction and can play an important regulatory role in cellular physiological and pathological reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of various extracellular factors on cell behavior is closely related to the activation of intracellular multiple signaling transduction pathways. Among them, activation of the JAK/STAT pathway in cell apoptosis has been widely studied in recent years (2628). The JAK/STAT signaling pathway is one of the important pathways of cytokine transduction and can play an important regulatory role in cellular physiological and pathological reactions.…”
Section: Discussionmentioning
confidence: 99%
“…There, these complexes bind to specific DNA sequences and alter their expression. In particular, there is good evidence that the IL-6/JAK/STAT3 pathway in tumor cells can be downregulated by glucocorticoids (eg, Kaymaz et al 26 ).…”
Section: Targeting Innate/humoral Immune/ Inflammatory Responsesmentioning
confidence: 98%
“…It has been showed that K562 when treated with curcumin inhibited Jak2 mRNA expression and down regulated the activity of STAT5a (Blasius et al, 2006). Similarly, a significant decrease was seen in STAT5A mRNA relative expression level at 48 hours of Methylprednisolone treatment (P<0.05) in K-562 cells (Kaymaz et al, 2012). When penicillin treatment was given K562, STAT5A expression was down regulated.…”
Section: Discussionmentioning
confidence: 80%